FRAMING DAN GENDER DALAM KEPATUHAN PAJAK : STUDI EKSPERIMEN - Titisari Dian Prastiwi; Theresia Woro Damayanti (Akuntansi dan Teknologi Informasi, 2019)
Framing causes differences individual behavior in making various decisions. One of them is the decision regarding tax compliance. This research study’s aimed to examine where there are differences in tax compliance behaviour between those who receive positive and negative framing and differences in individual tax compliance behavior based on personal attributes in the form of masculine and feminine gender. Prospect theory used as a basis for explaining changes in individual behavior when receiving framing effects. This study was conducted by primary data in the scope of Bachelor’s Degree of Accountancy at FEB UKSW who took Taxation Management. This experiment design was consisted of 2 x 2 between subject factorial designs. The result of this study prove that there is no influence between framing and gender on tax compliance.The results that obtained from the examination of interaction also prove that there is no influence that is difference between positive and negative framing and or masculine and feminine gender on tax compliance.